2019
DOI: 10.3390/ijms20235951
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase CK2 Subunits Differentially Perturb the Adhesion and Migration of GN11 Cells: A Model of Immature Migrating Neurons

Abstract: Protein kinase CK2 (CK2) is a highly conserved and ubiquitous kinase is involved in crucial biological processes, including proliferation, migration, and differentiation. CK2 holoenzyme is a tetramer composed by two catalytically active (α/α’) and two regulatory (β) subunits and exerts its function on a broad range of targets. In the brain, it regulates different steps of neurodevelopment, such as neural differentiation, neuritogenesis, and synaptic plasticity. Interestingly, CK2 mutations have been recently l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 54 publications
(82 reference statements)
1
37
0
Order By: Relevance
“…For cytoskeleton labeling, GN11 cells were seeded at a density of 5 × 10 3 cells/well in a 24-multiwell plate, two days after they were treated for 60/120 min with the different hormones and fixed with 4% paraformaldehyde-PBS for 15 min at RT and immunostained as previously described [ 35 ]. Briefly, fixed cells were then incubated with an anti-alpha-tubulin primary antibody at room temperature for 2 h, followed by an anti-mouse 488-conjugated secondary antibody at room temperature for 2 h. To detect F-actin, cells were treated with phalloidin-TRITC (1:400, in PBS) for 30 min at 37 °C before mounting with Mowiol.…”
Section: Methodsmentioning
confidence: 99%
“…For cytoskeleton labeling, GN11 cells were seeded at a density of 5 × 10 3 cells/well in a 24-multiwell plate, two days after they were treated for 60/120 min with the different hormones and fixed with 4% paraformaldehyde-PBS for 15 min at RT and immunostained as previously described [ 35 ]. Briefly, fixed cells were then incubated with an anti-alpha-tubulin primary antibody at room temperature for 2 h, followed by an anti-mouse 488-conjugated secondary antibody at room temperature for 2 h. To detect F-actin, cells were treated with phalloidin-TRITC (1:400, in PBS) for 30 min at 37 °C before mounting with Mowiol.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, CX-4945 has been found to strongly inhibit cell migration and differentiation [3]. These effects are strictly related to a rapid inhibition of CK2, since the reduction in phosphorylation of the main substrates of the kinase occurs within a few hours after CX-4945 administration [3,33,36]. Data obtained through a recent phosphoproteomic analysis performed in mitotic HeLa cells confirmed that CK2 is the main kinase target of CX-4945.…”
Section: Introductionmentioning
confidence: 96%
“…It is widely acknowledged that the Ser/Thr protein kinase CK2, a tetrameric holoenzyme composed of two catalytic α (or α') and a dimer of regulatory β subunits, is involved in the regulation of a plethora of biological processes and basal cellular functions, including growth, proliferation and differentiation, transcription and translation, glucose uptake, adhesion and migration [1][2][3][4][5][6][7]. This pleiotropy relays on the fact that CK2 is a ubiquitously expressed and constitutively active protein kinase, with hundreds of substrates widely distributed in most of the subcellular compartments [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, specific functions of α respect to α’ appear to play a role in the regulation of metabolic rewiring. CK2 isoform-specific substrates/partners/functions have been already reported [ 11 , 31 , 39 , 40 , 41 ]; further studies will be necessary to assess their effective implication in cancer cell metabolism and to identify novel targets and mechanisms that might be implicated. However, it is also important to notice that, as previously observed in other cell lines [ 31 ], the KOα clones display a reduction of the β CK2 regulatory subunit, which is not (or only marginally) appreciable in KOα’ cells ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%